2016
DOI: 10.3310/pgfar04050
|View full text |Cite
|
Sign up to set email alerts
|

Psychological approaches to understanding and promoting recovery in psychosis and bipolar disorder: a mixed-methods approach

Abstract: BackgroundRecovery in mental health is a relatively new concept, but it is becoming more accepted that people can recover from psychosis. Recovery-orientated services are recommended for adult mental health, but with little evidence base to support this.ObjectivesTo facilitate understanding and promotion of recovery in psychosis and bipolar disorder (BD), in a manner that is empowering and acceptable to service users.MethodThere were six linked projects using qualitative and quantitative methodologies: (1) dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 326 publications
(493 reference statements)
0
16
0
Order By: Relevance
“…mood appraisals, sleep, coping styles or psychotic experiences) . Indeed, there are very few high‐quality, randomized controlled trials of targeted psychological interventions that have been completed early in the course of BD . This is despite current cognitive models indicating that psychological interventions in BD may be more efficacious if delivered prior to the complicating effects of subsequent mood episodes .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…mood appraisals, sleep, coping styles or psychotic experiences) . Indeed, there are very few high‐quality, randomized controlled trials of targeted psychological interventions that have been completed early in the course of BD . This is despite current cognitive models indicating that psychological interventions in BD may be more efficacious if delivered prior to the complicating effects of subsequent mood episodes .…”
Section: Discussionmentioning
confidence: 99%
“…81 Indeed, there are very few high-quality, randomized controlled trials of targeted psychological interventions that have been completed early in the course of BD. 82,83 This is despite current cognitive models indicating that psychological interventions in BD may be more efficacious if delivered prior to the complicating effects of subsequent mood episodes. 82 Yet evidence is growing to improve our understanding of experiences early in the course of BD 84 and studies are emerging that will specifically assess the suitability and efficacy of targeted psychological interventions during the early phases of illness; e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we controlled for many variables that may have an impact on outcome, it is plausible that SGA and lithium or valproate initiators differed in terms of unmeasured covariates. It is conceivable, for instance, that the groups differed in characteristics independently related to likelihood of hospitalization, such as neuropsychological function or attitudinal, self‐management, or other features more amenable to qualitative analysis …”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable, for instance, that the groups differed in characteristics independently related to likelihood of hospitalization, such as neuropsychological function 35 or attitudinal, self-management, or other features more amenable to qualitative analysis. 36 Nonetheless, these population-based results provide complementary information to data from randomized controlled trials which are carried out under stringent protocol controls, with highly selected samples of volunteer participants. In postmarketing surveillance for drug safety, the optimistic story told by published clinical trials often contrasts with less favorable data from more inclusive populationbased studies, as has been shown for antipsychotics 37,38 and other drugs.…”
Section: Complementarity Of Controlled and Naturalistic Study Designsmentioning
confidence: 99%